Insights to Preventive Dentistry by Evaluating Lactoferrin for Caries Control and Periodontal Disease Prevention - Rehana Kausar; Maleeha Khurram; Shaher Bano; Tahmeena Atiq; Ammara Anwar; Attique Ur Rehman; Kanwal Fatima (Pakistan Journal of Medicine and Dentistry)
Background: Salivary defensins play an important role in periodontal disease prevention. This study evaluated the role of salivary lactoferrin, an antimicrobial peptide, in preventive dentistry by assessing its expression in caries and periodontal disease patients.